(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The emerging field of nanoscience and nanotechnology are becoming more and more popular nowdays. Nanotechnology involves manipulating and controlling atoms and molecules and design new materials, nanomachines and nanodevices for application in all aspects of our lives. The application of nanotechnology has enormous potiential to greatly influences the world in which we live. From consumer goods ,electronics, computers, information and biotechnology, energy, environment and medicine, all sectors of economy are impacted by nanotechnology.